2022
DOI: 10.3390/cancers14040887
|View full text |Cite
|
Sign up to set email alerts
|

Compared Efficacy of Adjuvant Intravesical BCG-TICE vs. BCG-RIVM for High-Risk Non-Muscle Invasive Bladder Cancer (NMIBC): A Propensity Score Matched Analysis

Abstract: Background: Intravesical immunotherapy with bacillus Calmette–Guerin (BCG) is the standard therapy for high-risk non-muscle invasive bladder cancer (NMIBC). The superiority of any BCG strain over another could not be demonstrated yet. Methods: Patients with NMIBCs underwent adjuvant induction ± maintenance schedule of intravesical immunotherapy with either BCG TICE or RIVM at two high-volume tertiary institutions. Only BCG-naïve patients and those treated with the same strain over the course of follow-up were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Data from these studies emphasize that response rates to BCG therapy were similar to those seen in primary tumors [ 63 , 73 , 74 , 75 ]. Interestingly, although not yet studied in post-CMT patients, various BCG strains were found to perform differently in high-risk NMIBC, with several studies showing the superiority of the BCG-TICE strain over RIVM [ 76 , 77 ]. Despite adequate BCG exposure, Weiss et al reported that 33% of patients had further NMIBC recurrences and 19% progressed to MIBC, respectively [ 75 ].…”
Section: Follow-up Regimen and Salvage Treatmentmentioning
confidence: 99%
“…Data from these studies emphasize that response rates to BCG therapy were similar to those seen in primary tumors [ 63 , 73 , 74 , 75 ]. Interestingly, although not yet studied in post-CMT patients, various BCG strains were found to perform differently in high-risk NMIBC, with several studies showing the superiority of the BCG-TICE strain over RIVM [ 76 , 77 ]. Despite adequate BCG exposure, Weiss et al reported that 33% of patients had further NMIBC recurrences and 19% progressed to MIBC, respectively [ 75 ].…”
Section: Follow-up Regimen and Salvage Treatmentmentioning
confidence: 99%
“…A recent study corroborated the important role of routine reTURB, followed by an adequate maintenance course of BCG in organ-sparing NMIBC patients [ 20 ]. Interestingly, reTURB was found to be associated with longer recurrence-free survival (RFS) in patients receiving TICE strain maintenance therapy than those using Connaught and RIVM [ 20 , 21 ]. However, it should be underlined that reTURB, which must be done on a patient who may still be suffering from the consequences of the last surgery, is an invasive and morbid technique that significantly lowers the patient quality of life.…”
Section: Introductionmentioning
confidence: 70%
“…Compared with initial TURB, reTURB can remove the residual tumors, detect understaging BC, improve the responsive rate of intravesical Bacillus Calmette-Guerin (BCG) instillation, and instruct further treatments [16][17][18][19]. A recent study corroborated the important role of routine reTURB, followed by an adequate maintenance course of BCG in organsparing NMIBC patients [20]. Interestingly, reTURB was found to be associated with longer recurrence-free survival (RFS) in patients receiving TICE strain maintenance therapy than those using Connaught and RIVM [20,21].…”
Section: Introductionmentioning
confidence: 94%
“…A previous report showed that when routinely performing re-TUR followed by a maintenance BCG schedule, TICE was superior to RIVM for RFS outcomes. Further studies addressing the type of BCG may also be needed in the future [ 40 ].…”
Section: Discussionmentioning
confidence: 99%